ANALISIS KRITIS TENTANG KERUGIAN ATAS PERATURAN RESTITUSI PPN YANG DISETAHUNAN - IRWAN IRWAN (Media Bisnis, 2014)
Speaking of VAT refunds we agree affairs will certainly be difficult. Various rules and Act has been in launch to facilitate Tax able Person (PKP) in VAT refunds but obstacles do remain. The occurrence of VAT refunds due to excess PKP pay VAT, input VAT where the larger number safter the Exodus subtract VAT. There are two ways to address the over payment of VAT, the first way of compensation, a second way of restitution. PKP many chose the first way. PKP consequences when doing continuous compensation of the cash flows is because it will happen funds deposited in the State Treasury, where as if it significant funds will be needed by the company (PKP) for use in its business activities. This paper will try to calculate the impact of the loss on delayed refunds. If excess tax money is stored in the form of savings or deposits, because if the VAT excess money held in the State Treasury, PKP does not earn interest.